Enhancing the Superconducting Properties of Magnesium Diboride Without Doping. Issue 9 (5th June 2013) - Maeda, Minoru; Kim, Jung Ho; Oh, Sangjun; Li, Wen Xian; Takase, Kouichi; Kuroiwa, Yoshihiro; Dou, Shi Xue; Takano, Yoshiki; Goyal, A.
<x xml:space="preserve">Abstract</x> Carbon doping is known to be very effective for enhancing the high‐field properties of magnesium diboride, MgB2, but not for the low‐field properties. Here, we report that both the high‐ and the low‐field properties can be improved simultaneously without doping by increasing the initial magnesium partial pressure, by simply reducing the size of the magnesium particles. It is shown that in situ processed bulk MgB2 sintered with fine magnesium powders has superior superconducting properties compared with a bulk sample fabricated using coarse magnesium lumps. The change in the lattice parameters was almost negligible; however, a clear increase in lattice strain can be observed for the sample sintered with fine magnesium powders. The increase in the lattice strain results in an enhancement of the high‐field properties. Furthermore, it has also been found that the low‐field critical current density is not reduced, but rather slightly increased for the fine magnesium powder sample. This is due to a closer linkage among the grains that drastically improves grain connectivity. These findings demonstrate that the initial growth mechanism of MgB2 is very crucial for its superior superconducting properties, and it especially indicates the importance of magnesium vapor pressure.